Implementation of Web-Based Student Achievement Applications in Senior High Schools in Indonesia - Hafidz, Mohammad Al; Puspitaningrum, Ari Cahaya; Prasetya, Muhammad Septama; Fitrani, Laqma Dica (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Obtaining student achievement provides benefits for schools for accreditation assessment, curriculum determination, feedback and policy. SMA N 1 Waru is a Senior High School in Indonesia in the National Reference School category which almost every year gets achievements. Currently, management of achievement data has not been carried out optimally, accumulated achievement data cannot be displayed, storage of supporting data is not organized, and the accuracy of the information produced is hampered. This research aims to implement a website-based student achievement application. The method used is in two stages, data collection and application development. The application development technique uses the Rapid Application Development (RAD) model. This research produces an application that has functionalities: master data (period, type of achievement, level of achievement/certification, class), teacher data collection, student data collection, achievement data collection (proposal and approval of achievements), user management, achievement reports, and achievement dashboards, as well as manage user user access. All functionalities have passed testing using the black box testing method. Implementation of applications using RAD can be done quickly and effectively so that the school gets the benefits of collecting achievement data at any time, achievement information can be accessed by anyone who needs it, the information produced is accurate, and has storage media for achievement supporting documents that can be well organized.